The Impact of Information Technology Support on the Use of E-Learning Systems at University - Aan Kanivia; Hilda Hilda; Alfri Adiwijaya; Muhammad Faizal Fazri; Sabda Maulana; Marviola Hardini (International Institute for Advanced Science & Technology (IIAST), 2024)
E-learning technologies at educational institutions like University of Raharja are essential in enabling flexible and accessible education in this period of significant digital revolution. This study examines how Information Technology Support (ITS) affects user satisfaction, perceived usefulness, perceived ease of use, and intention to reuse concerning e-learning systems efficacy. Unlike prior Technology Acceptance Model (TAM) based studies, this research emphasizes the specific role of ITS dimensions, such as infrastructure and technical training, in non Western educational contexts. This provides unique insights for improving e-learning systems in higher education. This study assesses the reactions of 500 users of University of Raharja e-learning system using Structural Equation Modeling (SEM) with the PLS technique. Results indicate that perceived ease of use and perceived usefulness are greatly increased by strong ITS, which in turn has a beneficial effect on User Satisfaction and Intention to Reuse. This study aligns with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) by enhancing the accessibility and quality of education through e-learning systems, SDG 9 (Industry, Innovation, and Infrastructure) by emphasizing the importance of robust IT infrastructure and technical training, and SDG 10 (Reduced Inequalities) by addressing the digital divide in non Western educational settings. Additionally, ITSs SDG 17 (Partnerships for the Goals) by encouraging collaboration between educational institutions, technology providers, and policymakers to optimize e-learning outcomes. According to the study findings, ITS must be strengthened to maximize e-learning system performance, raise user happiness, and promote continuous usage.